Herbicide protection pod technology for native plant restoration: one size may not fit all. Issue 3 (13th January 2021) - Baughman, Owen W.; Griffen, Jessica; Kerby, Jay; Davies, Kirk W.; Clenet, Danielle; Boyd, Chad
Abstract : Pre‐emergent herbicides are frequently used to control exotic annual plants prior to seed‐based restoration, but seeding must generally wait until herbicide toxicity has waned. The emerging seed‐enhancement technology of herbicide protection pods (HPP) allows for simultaneous seeding and herbicide application by protecting desirable seeds inside pods or pellets containing activated carbon, allowing for single‐entry and potentially cost‐saving wildland restoration approaches. This technology has shown promise in multiple recent lab and field experiments. However, the effect of pod size on efficacy has not been formally investigated, and important small‐seeded species have either not been tested or have shown less‐promising results when used with this technology. Using emergence trials in two different laboratory environments with two small‐seeded species important to restoration in the semi‐arid western United States (Wyoming big sagebrush [ Artemisia tridentata Nutt ssp. wyomingensis ] and Sandberg bluegrass [ Poa secunda J Presl]), we investigated if HPP size affected early performance and protection from herbicide (imazapic), as well as how different sizes of HPPs compared to bare seed. For both species, smaller HPP sizes selected to match optimal seeding depths showed up to two‐fold higher emergence and aboveground biomass than larger pellets and still maintained protection from herbicide toxicity. Both species also showed 50–90% reductions in emergence and aboveground biomass due to incorporation into HPPs in general, resulting in only one species (bluegrass) showing the desired effect of HPPs: higher success than bare seed in the presence of herbicide. We suggest that additional experimentation to improve this promising technology is warranted.